The Reuters Institute digital news report 2021 - Newman, N; Fletcher, R; Schulz, A; Andi, S; Robertson, C; Nielsen, R (Reuters Institute for the Study of Journalism, 2021)
The tenth Digital News Report from the Reuters Institute for the Study of Journalism at the University of Oxford reveals new insights about digital news consumption based on a YouGov survey of over 92,000 online news consumers in 46 media markets including India, Indonesia, Thailand, Nigeria, Colombia and Peru for the first time.